Heavy metal contamination of vegetables in urban and peri-urban areas. An overview - Fischer, Gerhard; Fischer-García, Franz Leonard (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2023)
The growth in urbanization and industrialization is causing an increase in environmental pollution in cities and their surrounding areas. Additionally, the growing urban population requires a greater volume of fresh vegetables. In nature, heavy metals (HM) are widely distributed; when they gradually enter the soil-plant-consumer continuum, they are difficult to remove from the system and accumulate at toxic levels. To gain an overview of this situation, the information in the ScienceDirect database was used in accordance with the PRISMA guide. For this, the keywords “vegetable”, “contamination” and “urban” were used in a first step and, in a second step, the keywords “vegetable” and “heavy metal” were used. The most toxic HM for consumers are Cd, Pb, Hg, Cr and As, as well as essential MP for the plant (Zn, Cu, Ni, Fe, Mo). At excessive concentrations these cause neurological and kidney damage, cancer and other forms of damage to health. Crop contamination can come from the atmosphere, irrigation water, and/or the soil itself, proximity to busy roads, industry, polluted rivers, and excessive use of pesticides and fertilizers that contain HM. Plant poisoning by HM causes a decrease in root growth and biomass of the plant, foliar chlorosis, and other physiological alterations. Leafy vegetables (including aromatic herbs) and solanaceous vegetables accumulate the most HM, while cucurbits and legumes are the least affected. Plants that develop for a longer time accumulate a greater amount of HM. In general, to increase the food safety of urban horticulture, more studies are needed on HM contamination, soil aptitude, risk assessment for ingesting intoxicated vegetables, as well as appropriate instructions for the clean handling of these crops in cities and surrounding areas.